Asociación de Mujeres Afro por la Paz: Feminism with the body and face of a woman - Zulver, JM (SAGE Publications, 2021)
The Asociación de Mujeres Afro por la Paz (Association of Afro Women for Peace—AFROMUPAZ) is an organization of displaced Afro-Colombian women now based in Bogotá. The organization represents a differential brand of feminism in the face of historical and ongoing violence and provides community, support, and employment opportunities for dozens of women and their families. Its “feminism with a woman’s body and face” is part of the landscape of popular feminism in the region, but its specific social location and its actions cannot be understood without a deliberate and critical understanding of race. La Asociación de Mujeres Afro por la Paz (AFROMUPAZ) es una organización de mujeres afrocolombianas desplazadas ahora radicadas en Bogotá. La organización representa un tipo distinto de feminismo frente a la violencia histórica y continua, y ofrece oportunidades comunitarias, de apoyo y de empleo para decenas de mujeres y sus familias. Su “feminismo en cuerpo y cara de mujer” es parte del panorama del feminismo popular en la región, pero la comprensión de su ubicación social específica y acciones requiere de un acercamiento deliberado y crítico de la cuestión racial.